Improving Science Process Skills and Student Cooperation Skills Using the POGIL Model Assisted by Animated Media - Sumanti, Fifi; Khairil Anwar; Nursina Sari (Journal for Lesson and Learning Studies, 2023)
Based on the previous literature review, applying the POGIL (Process Oriented Guided Inquiry Learning) model in elementary school learning still needs to be strengthened using animation media to achieve optimal learning goals. This research aims to analyze the effectiveness of using the POGIL model assisted by animation media regarding changes in science process and collaboration skills. This type of research is a quasi-experiment with a Non-Equivalent Control Group Design class design. The sample used was 58 students, consisting of 29 in the VA class as the experimental class and 29 in the VB class as the control class. The data collection instruments in this research were essay question sheets, observation sheets, and questionnaire sheets. The data analysis method used is inferential statistics with the t-test. The results of this research are that the use of the POGIL model assisted by animation media has very effective results on the science process skills and collaboration abilities of elementary school students as seen from the achievement and improvement of each indicator of science process skills which is classified in the very high category. Students' cooperative abilities in groups have increased significantly, resulting in relatively high scores. It was concluded that using the POGIL Model significantly improved elementary school students' science process skills and collaboration.